2019
DOI: 10.1371/journal.pone.0214500
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in livestock biosecurity practices amidst environmental and social uncertainty: Evidence from an experimental game

Abstract: Livestock industries are vulnerable to disease threats, which can cost billions of dollars and have substantial negative social ramifications. Losses are mitigated through increased use of disease-related biosecurity practices, making increased biosecurity an industry goal. Currently, there is no industry-wide standard for sharing information about disease incidence or on-site biosecurity strategies, resulting in uncertainty regarding disease prevalence and biosecurity strategies employed by industry stakehold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…In this study and in other published works [20,35,41] we have demonstrated the potential value of using experimental gaming simulations as a data gathering tool for use in categorizing behavioral strategies. Our experimental framework focuses on creating a digital representation of a complex decision mechanism in order to identify prevalent behavioral strategies.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…In this study and in other published works [20,35,41] we have demonstrated the potential value of using experimental gaming simulations as a data gathering tool for use in categorizing behavioral strategies. Our experimental framework focuses on creating a digital representation of a complex decision mechanism in order to identify prevalent behavioral strategies.…”
Section: Discussionsupporting
confidence: 53%
“…Our digital experiments simulated the management of a porcine facility's biosecurity in the face of a contagious disease. Our simulation was modeled after [41]. Our updated version follows a similar user interface (UI) and mechanics, with the added capability for online deployment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations